The good of spouses as object of simulation of the marriage consent - Leszczyński, Grzegorz (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The Code of Canon Law of 1983 classifies the reasons for marriage invalidity in three different categories: diriment impediments, defects in matrimonial consent and a lack or a defect of the canon form. In 1101 § 2 the Code of Canon Law enumerates different forms of simulations among different defects in matrimonial consent. Simulation signifies that a person contracting marriage expresses a marital agreement merely on the surface, excluding in reality through a positive act of the will the marriage itself or its essential element or an essential quality of the marriage. The present article is an attempt to look at the relation existing between the validity of marriage and the exclusion of the good of spouses, with the consideration of the object of the simulation form and the ways of delivering proof of it.